The role of career adaptability resources in dual career pathways: A person-oriented longitudinal study across elite sports upper secondary school. (July 2023) - Ojala, Juulia; Nikander, Aku; Aunola, Kaisa; De Palo, Jessica; Ryba, Tatiana V.
Abstract: Objectives: Obtaining education is an important milestone in athletes' preparation for their professional career after sport. Literature indicates that combining school and sport is not an easy task for many aspiring youth athletes. It has been proposed that career adaptability, which refers to psychosocial resources enabling individuals to solve complex occupational transitions, present and anticipated vocational development tasks, and career related challenges could be a relevant concept for applied work with student-athletes. In this study, we examined whether there are distinct developmental profiles of career adaptability among adolescent athletes across the upper secondary school years. We also investigated the associations between career adaptability and sport withdrawal and academic achievement. Design and methods: A total of 391 Finnish-speaking student-athletes completed the questionnaire on career adaptability (Career Adapt-Abilities Scale – Dual Career Form; Ryba & Aunola, 2015; Ryba et al., 2017) at the beginning and end of upper secondary school. The participants' background information about their sport participation and grade point average were collected upon completion of each grade of upper secondary school. The data were analysed using cluster analysis, cross-tabulation, and one-way analysis of variance. Results: Four distinct adaptability profiles were identified: higher adaptability, lower adaptability, increasing adaptability, and decreasing adaptability. Higher and lower adaptability profiles showed stable levels of adaptability across time, whereas the adaptability level either increased or decreased in the other two profiles. Student-athletes with a lower career adaptability profile were overrepresented among those who withdrew from competitive sports, and they reported lower grade point averages than those with higher scores of career adaptability. Conclusions: High scores of career adaptability were associated with high grades, whereas low scores of career adaptability were associated with low grades and a probability to withdraw from competitive sport. Therefore, it is recommended that career adaptability be considered as important self-regulation resources for sustaining dual career pathways over time. Highlights: Four different career adaptability profiles were identified in student-athletes. The developmental profiles separated after the first year of upper secondary school. Lower career adaptability resources were related to sport withdrawal. Higher career adaptability resources were related to high academic achievement.